Analisis de la carrera administrativa en Colombia. Caso Convocatoria 601 a 623 Docentes posconflicto 2018 - 2020 (2022)
This investigation identify different dificults that happened in 2019 and 2020 that not let Colombia implement Administrative carrrer as a technical system to manage the human talent serving the state, it was required to guide this dissertation from the stages of merit contest 601 and 623 Docentes Posconflicto organized by Comisión Nacional del Servicio Civil. It was esencial analized theoretical fundaments, normativity, past and evolution about Administrative Carreer. Then studies the merit, equality, opportunity, transparency, effectiveness and efficiency Constitutional principlies. Finally it was possible identify social, economic, politics factors that affected the merit contest